An indicial-polhamus model of aerodynamics of insect-like flapping wings in hover - Pedersen, C B (Cranfield University, 2011)
As part of the ongoing development of Flapping-Wing Micro Air Vehicle (FMAV) prototypes at RMCS Shrivenham,a model of insect-like wing aerodynamics in hover has been developed, and implemented as MATLAB code.The model is intended to give better insight into the various aerodynamic effects on the wing, so is as close to purely analytical as possible. The model is modular, with the various effects treated separately.This modularity aids analysis and insight, and will allow future refinement of individual parts. However,it comes at the expense of considerable simplification,which requires empirical verification. The model starts from quasi-steady inviscid flow around a thin 2D rigid flat wing section,accounting for viscosity with the Kutta-Joukowski condition,and the leading edge suction analogy of Polhamus. Wake effects are modelled using the models of Kussner and Wagner on a prescribed wake shape,as initially used by Loewy. The model has been validated against experimental data of Dickinson's Robofly, and found to give acceptable accuracy.Some empirically inspired refinements of the Polhamus effect are outlined, but need further empirical validation. This thesis comprises of six main parts: Part I is introductory material, and definitions, including an overview of what insect-like Rapping flight actually entails, and detailed definitions of the variables and terms used later. Part 2 describes the new theoretical model, and a simple scaling analysis of the forces and moments predicted. Part 3 deals with the MATLAB implementation of the above theory, and the considerations re-quired when adapting the theory for computational use. Part4 shows and discusses the results of the above code, against experimental measurements on Dickinson's Robofly. Part 5 is the conclusions, including a comprehensive list of all assumptions made in the theory. Part6 , the appendices, contain useful mathematical identities,and a copy of the code that was developed.